Evidence and. implications of massive erosion along the Strait of Istanbul (Bosphorus) - Gökasan, E; Tur, H; Ecevitoglu, B; Görüm, T; Türker, A; Tok, B; Çaglak, F; Birkan, H; Simsek, M (SPRINGER, 2005)
The Strait of istanbul (Sol) (Bosphorus) is a narrow valley, which has evolved tectonically from a stream, and in which thick sediment deposits have accumulated in the course of its evolution. Detailed seismic and multi-beam bathymetric data have revealed that the upper parts of the deeper channel deposits consist of parallel strata, which have mostly been eroded subsequently to their deposition. The resulting erosion surface is represented by the present channel floor in the strait, the estimated volume of the eroded material being approximately 2 x 10(8) m(3). Erosion rate and seafloor morphology indicate that the flow direction was from the south to the north. This inner channel may have been formed by an abrupt flooding of the Black Sea by Mediterranean waters at the beginning of the latest connection between the Marmara and the Black seas Subsequently, the Mediterranean bottom current of the modern two-way flow system, which was established at about 5-4 ka b.p., has given the latest shape to the strait floor.
Keywords: NORTH ANATOLIAN FAULT; BLACK-SEA SHELF; LATE QUATERNARY SEDIMENTATION; MARMARA SEA; GLACIAL-HOLOCENE; LEVEL CHANGES; SEISMIC DATA; TURKEY; STRATIGRAPHY; CONNECTIONS; Geology; Oceanography